Preoperative Halo-Femoral Traction With Posterior Surgical Correction for the Treatment of Extremely Severe Rigid Congenital Scoliosis (Cobb Angle >120°). Issue 9 (1st May 2022) - Zhang, Hongqi; Yang, Guanteng; Guo, Chaofeng; Deng, Ang; Xiao, Lige
Abstract : Introduction: To evaluate the effectiveness and safety of preoperative halo-femoral traction (HFT) with posterior surgical correction for the treatment of extremely severe rigid congenital scoliosis (>120°). Methods: We reviewed the records of all patients with extremely severe rigid congenital scoliosis (>120°) treated with preoperative HFT from 2010 through 2018. Radiographic measurements were performed. The period of traction, blood loss, operation time, complications, and pulmonary function test results were recorded. Results: A total of 11 patients were included in the study. All patients underwent preoperative HFT with posterior surgical correction. The mean preoperative main curve Cobb angle was 127.9° ± 4.4°, and the average correction rate was 33.5% posttraction, 54.8% postoperation, and 55.3% at the latest follow-up. Pulmonary function improved significantly after traction, and forced vital capacity and forced expiratory volume in 1 second increased from 34.7% and 33.4% to 48.1% and 48.5%, respectively. Only one patient experienced halo pin infection during HFT. No patients experienced permanent neurologic deficits or death. Conclusion: For extremely severe rigid congenital scoliosis with a Cobb angle greater than 120°, preoperative HFT with posterior surgical correction offers an effective and safe corrective option. The perioperative complication rate can be partially reduced. Study Design: Retrospective study.